MtSSPdb: The Medicago truncatula Small Secreted Peptide Database . Issue 1 (21st February 2020) - Boschiero, Clarissa; Dai, Xinbin; Lundquist, Peter Knut; Roy, Sonali; Christian de Bang, Thomas; Zhang, Shulan; Zhuang, Zhaohong; Torres-Jerez, Ivone; Udvardi, Michael K.; Scheible, Wolf-Rüdiger; Zhao, Patrick Xuechun
Abstract : MtSSPdb hosts a compendium of small secreted peptide sequences with annotations and an RNA-seq-based gene expression atlas for Medicago truncatula, a plant small secreted peptide prediction tool, and phenotyping data from synthetic peptide screens in planta. Abstract: A growing number of small secreted peptides (SSPs) in plants are recognized as important regulatory molecules with roles in processes such as growth, development, reproduction, stress tolerance, and pathogen defense. Recent discoveries further implicate SSPs in regulating root nodule development, which is of particular significance for legumes. SSP-coding genes are frequently overlooked, because genome annotation pipelines generally ignore small open reading frames, which are those most likely to encode SSPs. Also, SSP-coding small open reading frames are often expressed at low levels or only under specific conditions, and thus are underrepresented in non-tissue-targeted or non-condition-optimized RNA-sequencing projects. We previously identified 4, 439 SSP-encoding genes in the model legume Medicago truncatula . To support systematic characterization and annotation of these putative SSP-encoding genes, we developed the M. truncatula Small Secreted Peptide Database (MtSSPdb; https://mtsspdb.noble.org/ ). MtSSPdb currently hosts (1) a compendium of M. truncatula SSP candidates with putative function and family annotations; (2) a large-scale M. truncatula RNA-sequencing-based gene expression atlas integrated with various analytical tools, including differential expression, coexpression, and pathway enrichment analyses; (3) an online plant SSP prediction tool capable of analyzing protein sequences at the genome scale using the same protocol as for the identification of SSP genes; and (4) information about a library of synthetic peptides and root and nodule phenotyping data from synthetic peptide screens in planta. These datasets and analytical tools make MtSSPdb a unique and valuable resource for the plant research community. MtSSPdb also has the potential to become the most complete database of SSPs in plants.